북한이탈주민의 인권 보호 - 장복희(Bok-Hee Chang) (이화젠더법학, 2017)
북한은 국제사회에서 최악의 인권침해국가로 보고 있다. 제3국에서 떠돌고 있는 수만에서수십만에 달하는 탈북민은 인권사각지대에 놓여 있고 북한으로 강제 송환되고 있다. 탈출한북한여성도 강제혼인과 성매매대상이 되고 있고. 법적으로 인정받지 못한 혼인에서 출생한 아동들은 법적 신분이 모호하거나 중국에서 초등교육조차 받지 못하고 있다. 21세기는 소수자(취약계층) 보호의 시대이다. 북한이탈주민의 권리보호는 세계인권선언상의보편적 인권정신 실현과 국제인권법상 차별금지원칙, 평등원칙의 준수에서 시작되어야 한다. 국제법적 보호로는, 중국을 비롯한 북한이탈주민의 난민 지위 인정 및 일시적 보호가 필요하다. 탈북자는 난민협약상 협약난민의 지위에 있고, 사실상 난민으로서 UNHCR이 인정하는 위임난민을 부여 받았거나 현지난민 상황에 처해있으며, 고문방지협약과 자유권 규약 및 국제관습법상 일시적 보호와 북한으로의 강제송환금지의 대상이 된다. 중국은 이미 난민협약, 난민의정서, 고문방지협약에 가입하고, 자유권 규약에 서명한 상황이고, 이는 난민보호를 하겠다고 국제사회에 공약을 한 것이다. 이러한 점에서 한국 정부는 탈북난민이 가장 많이 체류하고 있는 중국에 대하여 국제법을 준수할 것을 촉구하는 외교적 노력을해야 한다. 북한주민과 북한이탈주민의 인권문제를 국제적으로 지속적으로 공론화하고 국제여론을 형성하여 북한이 가입하고 있는 국제인권조약과 관련규범의 준수를 유도하는 일과 이들을현장에서 돕고 있는 NGO 활동의 지원도 필요하다. 국내적 보호 방안으로는, 개인으로서의 보편적 인권 보장, 국민과 동등한 지위･권리보호 및소수자 보호와 구제, 무국적탈북자, 탈북여성과 무국적 탈북아동의 법적 보호, 북한이탈주민이관련 정책에 적극 참여할 수 있도록 하는 참여민주주의 실현이 중요하다. 요약하면 북한이탈주민 관련 법정책 방향은 지금까지의 주권적 접근과 냉전 사고에서 벗어나개인의 기본권을 보호하고 주권 중심에서 인권 중심의 전향적인 접근방법이 필요하다. 앞으로다양한 유형의 북한이탈주민 권리 관련 쟁점이 발생할 것이며 이에 대한 문제해결의 답은 궁극적으로는 국제인권법에서 찾아야 할 것이다. North Korea is regarded as the worst human rights violation nation in international community, and the numbers of North Korean defectors wandering in third countries reaching tens to hundreds of thousands, lie in the blind spot of human rights, and are forcibly repatriated to North Korea. The North Korean defectors women are also subject to forced marriage and prostitution. Children born out of legally unmarried marriage are either out of legal status or are not even receiving primary education in China. The 21st century is the age of minority protection. The protection of North Korean defectors' rights should begin with the realization of universal human rights in the Universal Declaration of Human Rights and the observance of the principle of non-discrimination under international refugee law and the principle of equality. For international legal protection, North Korean defectors require refugee recognition and temporary protection in other countries including China, They are in the status of refugees under the Convention on Refugees and are, in fact, granted refugee status recognized by the UNHCR called mandate refugees and sur place refugees. They can be also temporarily protected in range of Torture Convention and Covenant of Civil and Political Rights and international customary laws. National legal protection measures include protection of universal human rights as an individual, protection of status and rights equal to those of South Korean according to South Korea Constitution and domestic law, protection and relief of minorities, protection of stateless North Korean defectors and illegal North Korean defectors children etc. It is important to realize participatory democracy for them to participate themselves in their related policies. In summary, the policy making direction of the law related to the North Korea defectors of should go to protect the basic rights centered of individuals out of the sovereign approach and Cold War way of thinking. In the future, various types of issues related to North Korean defectors' rights will arise, and the answer to the problems should ultimately be found in international human rights law. KCI Citation Count: 3